Decoupling from yolk sac is required for extraembryonic tissue spreading in the scuttle fly Megaselia abdita - Caroti, Francesca; Noeske, Viola; Fath, Maike; Schütz, Lucas; Lemke, Steffen (eLife, 2018)
Extraembryonic tissues contribute to animal development, which often entails spreading over embryo or yolk. Apart from changes in cell shape, the requirements for this tissue spreading are not well understood. Here, we analyze spreading of the extraembryonic serosa in the scuttle fly Megaselia abdita. The serosa forms from a columnar blastoderm anlage, becomes a squamous epithelium, and eventually spreads over the embryo proper. We describe the dynamics of this process in long-term, whole-embryo time-lapse recordings, demonstrating that free serosa spreading is preceded by a prolonged pause in tissue expansion. Closer examination of this pause reveals mechanical coupling to the underlying yolk sac, which is later released. We find mechanical coupling prolonged and serosa spreading impaired after knockdown of M. abdita Matrix metalloprotease 1. We conclude that tissue-tissue interactions provide a critical functional element to constrain spreading epithelia.
Gesehen am 01.04.2019
Version of record published: November 12, 2018 (version 2)